Seguridad y protección en la unidad de imagenología para usuarios y trabajadores de la Clínica Central. Montería- Córdoba (2022)
This internship report was developed at the Central Clinic of the municipality of Monteria. The objective was to establish the elements of safety and protection in the imaging unit for patients and workers of the Central clinic. The methodology that was applied to said project was divided into four phases; the first was a diagnostic analysis, in phase 2 the information obtained in a 5W1H technique was systematized, in phase 3 the analysis of the documents that make up the radiological risk management manual was carried out in accordance with current regulations and they were socialized risks with internal and external stakeholders. In phase 4, an evaluation of the documents was made and a structure of the recommendations made was generated. From the results it was observed that the current regulations were not complied with and there was no relationship between what was planned and what was executed. Due to this, the risk manual was updated in its entirety and was entitled radiology protection manual. Divided into two parts: radiological surveillance and radiological protection. In conclusion, the risk manuals of the aforementioned clinic should be kept updated to improve the quality of the service offered.